SAT0011 Replication of A Distinct Psoriatic Arthritis Risk Variant at IL23R. (15th July 2016) - Budu-Aggrey, A.; Bowes, J.; Lohr, S.; Uebe, S.; Zervou, M.I.; Helliwell, P.; Ryan, A.W.; Kane, D.; Korendowych, E.; Giardina, E.; Packham, J.; McManus, R.; et al.
Abstract : Background: Psoriatic arthritis (PsA) is an inflammatory arthritis that is associated with psoriasis. Although the majority of PsA genetic risk loci identified also confer risk for psoriasis, we have recently reported evidence of loci that are associated with PsA and not psoriasis, including an association at the IL23R locus which is also independent of a psoriasis variant at the same locus. Methods: The PsA-specific SNP rs12044149, and the psoriasis SNP rs9988642 at the IL23R locus were genotyped in a cohort of 914 PsA cases and 6, 945 controls from Spain, Crete, Germany and the UK, with the Life Technologies QuantStudio genotyping platform. Association testing was carried out using PLINK, and a meta-analysis was performed with PsA Immunochip data (1, 962 cases, 8, 923 controls). Genotype data was also available from the psoriasis WTCCC2 study (excluding known PsA, n=1, 784) to compare effect sizes between PsA and psoriasis using multinomial logistic regression in Stata, and to directly compare PsA and psoriasis genotypes. Credible SNP sets were calculated for the PsA and psoriasis IL23R associations using the Bayesian refinement method, and functionally annotated. Results: We replicated the association rs12044149 with PsA ( P =4.03x10 –6 ), which remained significant when conditioning upon the psoriasis variant, rs9988642 ( P cond =4.86x10 –6 ), and reached genome-wide significance during meta-analysis of the combined PsA dataset ( P meta =4.76x10 –20 ). Only a modest association was found for rs9988642 ( P =0.04), with no genome-wide significance found during meta-analysis ( P =4.61x10 –4 ). Within the psoriasis dataset, this association remained significant when conditioning upon rs12044149 ( P =1.0x10 –07 vs. P cond =1.63x10 –5 ). Effect estimates for rs12044149 were significantly different between PsA and psoriasis ( P =2.0x10 –3 ), and direct comparison of genotypes for PsA and psoriasis found the risk allele to be significantly increased in PsA ( P =4.52x10 –4, OR=1.3). Credible SNPs for rs12044149 mapped to promoter and enhancer regions within memory CD8 + T cells, which we have previously reported to be critical for PsA. Conclusions: We have successfully replicated a PsA-specific (associated with PsA but not psoriasis) risk variant at the IL23R locus in an independent cohort, confirming rs12044149 to be distinct from rs9988642 (r 2 =0.02). This gives five PsA-specific associations that have now been identified. Disclosure of Interest: None declared